GIVING BIRTH TO THE NEW MAN. THE VOICES OF THE REVOLUTIONARIES IN THE 70S IN MODERN ARGENTINA (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
In this text we will analyze the objectives and argument of the book "The revolutionaries. Militancy, daily life and affectivity in the seventies "by Alejandra Oberti published in the year 2015. We will try to establish the links between this work and other productions with which the author dialogues, questioning many myths about the recent past in our country.
Keywords: gender; memories; military political organizations; recent past